Optimalisasi Efisiensi Energi Melalui Perapihan, Gambar Dan Perbaikan Instalasi Listrik Di Ruang Kelas Lantai 1 - Sunardi; Woro Agus Nurtiyanto; Rifa`i Harahap (AMMA : Jurnal Pengabdian Masyarakat, 2024)
In Industry 4.0 which is currently developing, it is very easy for us to create concept designs through calculations using software and also simulations using application software for computer programs, and we as Electrical Engineering Students at Pamulang University want to implement the Tri Dharma of Higher Education, one of which is carrying out community service by theme: "Optimizing energy efficiency through tidying, drawing and repairing electrical installations in classrooms on the 1st floor of the Markaz Hadits Legok Islamic Boarding School." Which requires a comprehensive approach. This process involves precise electrical design drawings, accurate electrical power calculations, as well as providing knowledge on how consultants work to design and calculate electricity by applying electrical formulas obtained during lectures and also providing knowledge on how skilled electrical contractors work appropriately. with knowledge and application of electrical installation standards. Work safety is a crucial aspect in carrying out these repairs, with calculations, simulations and compliance with relevant electrical installation standards. These steps aim to achieve an optimal electrical system, focusing on energy efficiency and comfort in the learning environment of the Markaz Hadits Legok Islamic Boarding School.